Arduino Based Automatic Banana Chip Slicer - Yunan, Amsar; Yanti, Yulisda; Khairuman, Khairuman; Anugreni, Fera; Bean, Hasbaini (PERFECT: Journal of Smart Algorithms, 2024)
Banana is a herbaceous fruit plant, in Latin banana Musa spp which belongs to the Musaceae family from Southeast Asia. What is meant by superior varieties is that banana plants are strong enough to withstand pests and diseases so they are capable of high production. Nowadays, many people who slice bananas still use simple or manual tools to slice raw bananas. An efficient machine mechanism must be needed in the manufacturing process to get these thin banana slices. This tool aims to avoid hand injuries and banana sap getting on your hands if you use a manual banana slicer. The working method of this tool is controlled by Arduino Uno R3 using an Ir sensor and with an output in the form of a relay which functions as a switch to rotate the blade. This test was carried out fifty times using three different types of bananas, namely, wak bananas, kapok bananas, and flower bananas. The results of testing three types of bananas, namely weak bananas, kapok bananas, and flower bananas, have the same thickness level, namely 1mm. This tool concludes that it makes it easier for people to slice bananas from manual to automatic so that the thickness is the same. The tool works based on input from two IR sensors using an analog signal pin connected to Arduino. The two IR sensors will detect if there is movement near the container.